DESCRIPTION OF A NEW SPECIES OF LAMPROGLENA (COPEPODA: LERNAEIDAE) FROM KERALA - Thomas, Shaju; Hameed, Shahul (Indian Journal of Fisheries, 2011)
A copepoc! parasite, Lamproglena krisliiiai sp. nov., collected from the gills of Clwniia strial.is (Bloch) at Cochin is described in detail. The new species is compared with the known species of the genus